UPAYA KEPALA DESA DALAM MENINGKATKAN PELAYANAN KEPADA MASYARAKAT DESA MOPU KECAMATAN BUKAL KABUPATEN BUOL - Ria, Satria; Sondeng, Ahmad; Sulastri (STISIPOL Mujahidin Buol, 2025)
This study aims to describe the efforts of the Mopu Village Head, Bukal District, Buol Regency, to improve public services. The underlying cause is low service quality, characterized by poor procedural communication, minimal staff training, and limited infrastructure. The method used was descriptive qualitative, using observation, interviews, and documentation techniques. Informants included the village head, staff, and the community. The results indicate that the Village Head has implemented public service standards, including procedures, timeframes, facilities, and staff competency. However, obstacles remain, such as low public understanding, limited human resources, and limited technological facilities. Despite this, the community appreciates the service improvements, particularly in terms of transparency and convenience. In conclusion, the Village Head's efforts have shown progress, but further strategies are needed to strengthen staff capacity, modernize systems, and disseminate procedures.